Analisis Yuridis Penerapan Ultra Petita dalam Putusan Mahkamah Konstitusi di Indonesia - Firdaus, Agam (UIN Jakarta, 2025)
This paper is to explain the implementation and implications of ultra petita in the decisions of the Constitutional Court (MK) in Indonesia. Although theoretically constrained by the boundaries of the request (petitum), in practice, the MK often rules beyond what is requested to fulfill the values of substantive justice and the constitution. This study uses a social construction approach to law to see how these decisions are produced and interpreted.